Síntese e caracterização de hidrogéis de poliacrilamida e metilcelulose para liberação controlada de pesticidas - Aouada, Fauze Ahmad (Universidade Federal de São Carlos, 2009)
In this thesis, the preparation and characterization of hydrogels of methylcellulose (MC) mechanically supported in polyacrylamide (PAAm) network for controlled release of pesticide were reported. The controlled release of pesticide paraquat was investigated using UV-Visible spectroscopic technique. The results showed that the presence of MC increased the flexibility of the matrixes. By varying of acrylamide (AAm), cross-linker and MC concentrations, it was possible to obtain hydrogels with mechanical and hydrophilic properties controlled and optimized for some specific application. The swelling degree values varied from 10 to 210 g/g. The mechanical properties values (maximum compressive stress and modulus of elasticity) varied from 0.55 to 22.33 kPa and from 1.06 to 27.50 kPa, respectively. The kinetic and structural properties were strongly influenced by the AAm, MC, pH and ionic strength of swelling medium. The kinetic release control of pesticide (until 30 days) could be adjusted by controlling the wateruptake of the hydrogels through the AAm/MC ratio. Hydrogels based on PAAm and MC polymers could be considered as promising materials for application in agriculture, in special, controlled release of agrochemicals.
SYNTHESIS AND CHARACTERIZATION OF METHYLCELLULOSE POLYSACCHARIDE AND POLYACRYLAMIDE HYDROGELS FOR CONTROLLED RELEASE OF PESTICIDES
Keywords: Físico-química; Hidrogéis; Liberação controlada de pesticida; Polímeros biodegradáveis; Metilcelulose; CIENCIAS EXATAS E DA TERRA::QUIMICA